Sustainable Islands Water Supply - Lidija Runko Luttenberger (Politehnika, 2017)
The islands are exposed to the ever increasing pressures of construction development, particularly of tourist facilities and accompanying service infrastructure which commands for the provision of sufficient quantity of drinking water. The problem of water supply is presently solved by displacing water, mainly by laying water supply pipelines fed by water from abundant coastal aquifers. The paper analyses the difference between water management on the side of supply and that on the side of demand, presents decentralized technologies and water reuse, specifies island experiences worldwide, reviews ecological issues related to desalinization, and proposes an optimum approach to water management for Croatian islands, placing an emphasis on the role of education. The Republic of Croatia should devise and develop a model of sustainable water management on its islands and spread it gradually to coastal territory and the mainland.